Arbitral interpretation of investment treaties: Problems and remedies for the debate on legitimacy (2019)
The last couple of decades have seen a considerable increase in the submittal of investment claims to Arbitral Tribunals, a process which has often been linked to the “proliferation” of investment treaties. Alongside, a debate on the so-called “legitimacy” of the Investor-State dispute settlement mechanism has emerged - and prompted calls for reform - refusing, for the moment, to go away. Treaty interpretation has not been in the forefront of discussion. Authorized (“authoritative”) interpretation - as performed by Arbitral Tribunals - is perhaps one of the issues of least (if any) concern. This Article explores the multiple issues arising from vesting excessive significance in authorized interpretations of Investor-State Arbitral Tribunals (in the events in which States Parties to the relevant investment treaty do not have opposing views on the construction of a conventional clause) vis-à-vis the distinction between authentic and authorized interpretation. Drawing on the referral to the notable cases in which this issue has arisen, this Article will present a few recommendations. © 2019 Centro Universitario de Brasilia. All rights reserved.